Tennessenoid A, an Unprecedented Steroid−Sorbicillinoid Adduct From the Marine-Derived Endophyte of Aspergillus sp. Strain 1022LEF - Zhao, Dong-Lin; Wang, Hai-Su; Gao, Li-Wei; Zhang, Peng (Frontiers in Marine Science, 2022)
Marine natural products, characterized by fascinating drug-like functionalities and promising biological activities, are important base materials for innovative drugs and agrochemicals. Chemical investigations of the marine-algal-derived endophytic fungus Aspergillus sp. 1022LEF residing in the inner tissue of marine red alga yielded a novel polyketide-terpene hybrid metabolite, namely tennessenoid A (1), as well as six known biosynthetic congeners including two steroids, ergosta-4,6,8(14),22-tetraen-3-one (2) and (22E,24R)-3α-ureido-ergosta-4,6,8(14),22-tetraene (3), and four sorbicillinoid-based compounds, saturnispol G (4), trichodimerol (5), and dihydrotrichodimer ethers A and B (6 and 7). Their structures were unambiguously determined based on extensive 1D/2D NMR and HRESIMS spectroscopic analyses. Tennessenoid A (1) was characterized as an unprecedented steroid−sorbicillinoid adduct via a C−C bond, which was rarely-observed in natural products. All of the isolated compounds were evaluated for their antifungal activities against eight plant pathogenetic fungi. 1, in particular, demonstrated broad-spectrum activities against Sclerotium rolfsii Sacc., Fusarium oxysporum (Schl.) F.sp cucumerinum Owen, Coniella diplodiella Petrak et Sydow, Physalospora piricola Nose., Fusarium graminearum schw., Alternaria mali rob., Colletotrichum orbiculare Arx., and Alternaria porri (E11iott) Cifed., with the inhibition zone diameters ranging from 2 to 7 mm.